Phase diagrams in blends of poly(3-hydroxybutyric acid) with various aliphatic polyesters (eXPRESS Polymer Letters, 2011)
Phase behavior with immiscibility, miscibility, crystalline morphology, and kinetic analysis in blends of poly(3-hydroxybutyric acid) (PHB) with aliphatic polyesters such as poly(butylene adipate) (PBA), poly(ethylene adipate) (PEA), poly(trimethylene adipate) (PTA), or poly(ethylene succinate) (PESu), respectively, were explored mainly using differential scanning calorimeter (DSC) and polarized-light optical microscopy (POM). Immiscibility phase behavior with reversible upper-critical-solution-temperature (UCST) is common in the PHB/polyester blends. The polyester/polyester blend of PHB/PTA is partially miscible with no UCST in melt and amorphous glassy states within a composition range of PTA less than 50 wt%. The miscible crystalline/crystalline blend exhibits ring-banded spherulites at Tc = 50~100°C, with inter-ring spacing dependent on Tc. All immiscible or partially miscible PHB/polyester blends, by contrast, exhibit disrupted ringbanded spherulites or discrete spherical phase domains upon cooling from UCST to crystallization. The blends of PHB with all other aliphatic polyesters, such as PESu, PEA, PBA, etc. are only partially miscible or immiscible with an upper critical solution temperature (UCST) at 180~221°C depending on blend composition. UCST with reversibility was verified.